Penentuan Kebutuhan Pupuk Kalium untuk Budidaya Tomat Menggunakan Irigasi Tetes dan Mulsa Polyethylene - , Amisnaipa; Anas D. Susila; Rykson Situmorang; D. Wasgito Purnomo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
Tomato var. Ratna was grown with polyethylene mulched and drip irrigation on Inceptisol Dramaga with very low soil K and organic matter during two seasons to K critical concentration, and potassium fertilizer requirement. Experiment used single location approach with three steps of activity. The first experiment was established in 2004 to develope artificial soil K status by adding K: 0X (0), 1/4X (193.098), 1/2X (386.195), 3/4X (579.293) and X (772.39 kg K2O ha-1), where X was amount of K equal to 772.39 kg K2O ha-1 or 1287.32 kg KCl ha-1. The second experiment was calibration K study, the experiment arranged in split plot design, with main plot was K status (form first experiment) and sub-plot was K aplication (0, 40, 80, 160, and 320 kg K2O ha-1) in 4 replicated. Third experiment was optimation of K rate. The result showed that interval of soil K availability extracted by Morgan Vanema was divided 5 classes, they were very low (< 58.25 ppm K), low (58.25-103.25 ppm K), medium (103.25-205.00 ppm K), high (=205 ppm K) and very high (>205.00 ppm K). Potassium recommendation for tomato on Inceptisol with drip irrigation and polyethylene mulch which has very low, low, medium, high and very high K content was 180.20, 131.30 and 82.25 kg K2O ha-1or equal to 300.33, 218.83, and 137.08 KCl ha-1 respectively. Key words: Fertilizer, Potassium, calibration, Lycopersicon esculentum.